Ecoprint Trainning for Cadres and People with Mental Disorders Families - Juwariah, Titik; Widi Ashari, Denny Rakhmad; Priyanto, Agus; Wahyuningsih, Diyan; Santoso, Edi (STIKes Patria Husada Blitar, 2024)
Mental disorders are health problems that affect the quality of life. The presence of People with Mental Disorders in the family affects financial capacity because destructive behavior increases the financial burden. Improving health is an investment in development through productive social and economic life. Efforts to improve health must be carried out together with increasing family economic independence. Ecoprint is a business choice because it is environmentally friendly and in demand by the community. This community service activity carries the theme of economic independence for People with Mental Disorders families by optimizing the role of cadres as drivers through Ecoprint entrepreneurship. Cadres are given entrepreneurship training, until a business unit is realized. Furthermore, cadres become the driving force for People with Mental Disorders families to be trained to make ecoprints to become a source of income. The purpose of the activity was to increase participants' knowledge and skills in making ecoprints. The activity was carried out for 2 days. The results showed an increase in participant knowledge from an average pretest of 56.7 to 82.1 posttest. There was an increase in cadre skills, the production results were 20 tote bags and 10 pieces of ecoprint cloth that were ready to be marketed. Ecoprint has great potential to be in demand by the market because it follows fashion trends and is considered environmentally friendly. Optimal support from all parties is highly expected for the smooth running of cadre assistance efforts in realizing the economic independence of People with Mental Disorders families.